Analysis of Fixed Asset Accounting Following Changes in the Status of State Universities as Legal Entities (PTNBH) - Hertrianto, Indra Prihatma; Poernamawatie, Fahmi; Hertanto, Ronny Hendra; Hastuti, Sri (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to analyze the accounting treatment of fixed assets following the change in status of Malang State University to a State-Owned Legal Entity Higher Education Institution (PTNBH). This change in status requires a transition from Government Accounting Standards (SAP) to Financial Accounting Standards (SAK), particularly PSAK 16 and ISAK 35. The research focuses on the calculation of depreciation expenses for fixed assets as determined in the Initial Asset Value (IAV). Data was collected through interviews and documentation, which were then analyzed using a descriptive case study approach. The research results indicate irregularities in depreciation charges, both too high and too low, primarily caused by the calculation method in the SIMAK BMN system. To address this, a prospective approach in accordance with PSAK 25 was applied. This adjustment includes the establishment of new useful lives, new book values, and new depreciation bases. Significant differences in depreciation charges between 2022 and 2023 were also found, primarily due to corrections for past errors. This study emphasizes the importance of validating asset data and selecting appropriate accounting methods to support the transparency and accountability of PTNBH's financial statements